Strategic Digital Marketing Innovation for Sustainable Growth of Traditional Food MSMEs in Indonesia - Ardhitya Alam Wiguna; Aditya Nizar Al Ardi; Dinu Saadillah; Financia Mayasari; Rini Hardiyani; Dicky Andriyanto; Nur Azizah (Indonesian Journal Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economic development; however, many face challenges in maintaining competitiveness, particularly in the traditional food sector. One example is the Putri Madu Cassava Tape Business in Jember Regency, East Java, which has experienced a decline in sales even though it has a wide market network. This study aimed to formulate an effective marketing strategy by combining SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis and Quantitative Strategic Planning Matrix (QSPM). The literature review highlighted the importance of strategic management, marketing mix, digital marketing, and empirical findings related to the competitiveness of MSMEs. Data was collected through interviews, questionnaires, and documentation involving business owners, employees, and marketing experts. The SWOT analysis identified key strengths such as product quality and an extensive distribution network, as well as weaknesses in the form of limited product innovation and conventional promotion. External analysis showed opportunities from digital technology adoption and government support, accompanied by the threat of fierce competition and changing consumer preferences. The QSPM results prioritized six alternative strategies, with digital marketing integration (TAS: 6.52) and product diversification (TAS: 6.20) as top priorities. These findings showed that the combination of SWOT–QSPM with digital marketing can provide a strategic framework for MSMEs to increase competitiveness, expand the market, and achieve sustainable growth.